Prospective associations of COVID-related stress with vaping nicotine and cannabis among high school students: Mediated by vaping susceptibility - Lee, Ryan; Cho, Junhan; Bae, Dayoung; Albers, Larisa; Herzig, Shirin Emma; Ramirez, Carla Michelle; Carvajal, Alberto, Jr; Soto, Daniel; Unger, Jennifer B. (PLOS ONE, 2025)
Adolescent e-cigarette and cannabis vaping have become significant public health concerns, with rates increasing in recent years. However, there is limited research on the impacts of COVID-related stress on adolescent vaping. This study examined the longitudinal impacts of COVID-related stress on adolescent e-cigarette and cannabis vaping, including the mediating role of vaping susceptibility (which measures a lack of a firm commitment not to use a substance). We examined the prospective associations of COVID-related stress during remote learning (2020–2021) with e-cigarette and cannabis vaping use two years later (2022–2023) through the mediation of vaping susceptibility (2021–2022) among a cohort of students recruited as ninth graders from nine public high schools across Los Angeles County and surveyed annually (N = 1,316). Higher levels of COVID-related stress were prospectively associated with increased susceptibility to vaping e-cigarettes (B = 0.04, p = .02) and cannabis (B = 0.04, p = .02) one year later, which in turn increased the odds of e-cigarette (B = 0.98, p = .003) and cannabis (B = 1.62, p < .001) vaping two years later. This study highlights the critical need for effective, school-based prevention programs to reduce susceptibility to vaping, particularly during periods of heightened stress or future crises.